PURSE-SEINE AND BOAT-SEINE JHANGU VALA) FISHERY FOR THE OIL SARDINE OFF COCHIN-1968-1971 - Balan, V (Indian Journal of Fisheries, 2011)
The data on the catches, fishing eflFort, length and sex composition relating to the purse seine fishery for the oil sardine, Sardinella longiceps V^l. off Cochin, during the three seasons from 1968-69 to 1970-71 are presented. A comparison of catch rates of the sardine landed by this gear with those of the boat seine thmgu vala during the same period has been made. A comparative study of the length range, the modal and the mean length distributions of the oil sardine catches obtained in the two gear revealed a fairly good similarity. Application of Chi-square test on the sex composition data of the sardine shoals fished by purse seine during 1969-71 indicated that there was no significant dominance of either sex